The Electricity Creation by the Means of Hydro Power Plant (International Journal of Innovative Research in Computer Science & Technology, 2022)
Energy can be produced in a variety of  ways, and electricity is one of them. Hydropower plants  produce electricity from water, thermal power plants  produce electricity from heat, wind energy power plants  produce electricity from wind, and geothermal energy  plants produce electricity from surface heat. The merits,  limits, and uses of the hydro power plant energy producing  process were discussed in this article. Hydro power plants  are one of the most well-known, efficient, and beneficial  energy producing processes. Water is a cost-effective and  efficient renewable energy source for power generation.  Water-based energy generation has been around for  decades and has shown to be a more efficient and effective  way to generate power. Dammed reservoirs, run-of-river,  pumped storage, in-stream technology, and new  technology gravitational vortex are five types of  technologies that may be employed to boost power  capacity in hydro power plants. The capacity category is  further broken down into big power, small power, mini  power, and micro and pico hydropower. Advanced  technology could not be placed since villages were not as  developed as they are now; nevertheless, as villages and  countries grow, they are increasingly turning to hydro  power plants as a source of electricity, which is growing  more popular due to its low cost and efficacy. This  document gives an overview of hydroelectric power plants  for generating energy, as well as information on  hydropower systems and the best turbines to employ.
Keywords: Hydropower; Reservoir; River; Turbines; Thermal